Good Environmental Governance in Indonesia (Perspective of Environmental Protection and Management) - Purniawati Purniawati; Nikmatul Kasana; Rodiyah Rodiyah (The Indonesian Journal of International Clinical Legal Education, 2020)
This paper discusses good environmental governance in the framework of environmental protection and management. The evironmental view of governance itself provides a conceptual framework in which public and private behavior is regulated in supporting more ecologically oriented arrangements. The framework forms a reciprocal relationship between the community (global, regional, national and local) in dealing with the access and use of environmental goods and services and binds them (at any level) with certain specific environmental ethics. Then as a system, Environmental Governance consists of socio-cultural aspects, political and economic interactions among many actors in civil society. In managing and protecting the environment around it is needed cooperation between humans, humans are very important to manage and protect the environment in which they live. Starting from the government and until the people have the same rights and obligations in managing and protecting the environment without exception. Not limited wherever domicile. Both rural communities, rural and urban areas, become an important part of the realization of a good and healthy environment. The existence of the community will be very effective if its role in controlling the management of the exis ting environment.